Analisis Kesulitan Guru Matematika Dalam Menerapkan Pembelajaran Secara Daring Selama Pandemi Covid-19 - Siti Latifah; Dadang Rahman Munandar (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2022)
The purpose of the study was to find out how difficult mathematics teachers in applying online learning during the covid-19 pandemic in SMPN 1 Karawang Timur. This type of research is skinative research. The research subject is a math teacher at SMPN1 Karawang Timur kleas VII. Data collection using interview guidelines and documentation. Based on the above explanation, it can be concluded that the difficulties experienced by math teachers in class VII in SMPN 1 Karawang Timur are : teachers find it difficult to motivate students, difficult to determine teaching materials, difficult to make learning aids due to lack of IT mastery, difficult to create an effective learning atmosphere because students who are not active then find it difficult to determine learning models and difficult to convey material, and it is difficult to know condition of students while studying. As for the way to overcome the difficulties of math teacher class VII in SMPN 1 Karawang Timur, namely: using whatsapp and contacting or calling the parents of students.Keywords: covid-19, Difficulty of math teachers, Online learning.